Microstructure, physical and mechanical properties of kaolin - diatomite composite reinforced with CaCO3 (2019)
The present work reports the microstructure, physical and mechanical properties of a material composed of kaolin, diatomite and calcium carbonate reinforcement (CaCO3). The ceramic prototypes were shaped by the slip casting method and sintered at temperatures between 800 °C and 1100 °C. The morphology and average pore size was analyzed by Scanning Electron Microscopy (SEM) and the mineralogical phases were determined by X-Ray Diffraction (XRD). The apparent density was established by the mercury immersion method according to the E – 8B Standard of the Institute of Ceramic Technology (ITC); the percentage of absorption was determined by the boiling method according to ISO 10545-3 standard; linear contraction was studied in three directions: long, wide and high. The study of the mechanical resistance to compression followed the procedure established at ASTM C773–88 standard and the breaking modulus was calculated by the three-point bending test, according to ISO 10545–4. Results show that the material structure is affected with increasing temperature reporting a decrease in quartz phase from 51.16 % to 33.81 %. Percentage of absorption revealed its most significant variation between 950 °C and 1100 °C with a decrease of 21 % approximately. Mechanical resistance values showed wide dispersion which was attributed to the different orientations in which the material failed during each test. According to the pore diameters found, the compound is characterized by being macro and mesoporous facilitating its application in catalysis, photochemistry, microelectronics and other microfiltration media